SERELAXIN IN THE STRATEGY OF MANAGEMENT THE PATIENTS WITH ACUTE DECOMPENSATED HEART FAILURE: FROM DECREASING OF SYMPTOMS TO THE IMPROVEMENT OF SURVIVAL - I. V. Zhirov; S. N. Tereschenko (Евразийский Кардиологический Журнал)
In this review data of clinical investifation of serelaxin were briefly outlined. In these trials administration of serelaxin just after admission in the hospitals was acoompanied by middle-term improvement of survival of patients with acute heart failure.